Avant-Garde Nationalism at the Dublin Gate Theatre, 1928-1940 - Beuken, Ruud van den (Book collections on Project MUSE., 2021)
"While the Dublin Gate Theatre (est. 1928) has become renowned for introducing experimental foreign drama to Ireland, this study is the first to analyse how the Gate also sought to become a site of avant-garde nationalism and to contribute to Irish identity formation in the nation's first post-independence decades"--